2019
DOI: 10.3390/metabo9060116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Serum Metabolic Fingerprint of Different Exercise Modes in Men with and without Metabolic Syndrome

Abstract: Exercise plays a beneficial role in the treatment of metabolic syndrome (MetS). Metabolomics can provide new insights and facilitate the optimization of exercise prescription. This study aimed to investigate whether the response of the human serum metabolic fingerprint to exercise depends on exercise mode or the presence of MetS. Twenty-three sedentary men (nine with MetS and fourteen healthy) completed four trials: Resting, high-intensity interval exercise (HIIE), continuous moderate-intensity exercise (CME),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…At lower exercise intensities (50%-60% VO 2 max), fat and carbohydrate oxidation both contribute to ATP generation. At higher exercise intensities (>60% VO 2 max), glycolysis is enhanced, with acidosis, a decrease in free Coenzyme A (CoA) and free carnitine, and accumulation of acetyl-CoA [19,20]. The data from our study showed log2-fold increases of 1.5 and 1.7 for the C2/C0 ratio, which might reflect activity of the mitochondrial enzyme carnitine acetyltransferase (CAT).…”
Section: Acylcarnitinesmentioning
confidence: 51%
“…At lower exercise intensities (50%-60% VO 2 max), fat and carbohydrate oxidation both contribute to ATP generation. At higher exercise intensities (>60% VO 2 max), glycolysis is enhanced, with acidosis, a decrease in free Coenzyme A (CoA) and free carnitine, and accumulation of acetyl-CoA [19,20]. The data from our study showed log2-fold increases of 1.5 and 1.7 for the C2/C0 ratio, which might reflect activity of the mitochondrial enzyme carnitine acetyltransferase (CAT).…”
Section: Acylcarnitinesmentioning
confidence: 51%
“…Until now, several studies have examined both the acute [19][20][21][22][23][24][25][26][27][28][29] and chronic [30][31][32][33][34][35] effects of exercise on the human metabolome by using metabolomics. Although blood represents the most widely used biofluid in metabolomics research [15], recent publications have demonstrated the ability of urine as a non-invasive biological material to reflect acute exercise-induced perturbations in metabolism, e.g., after short-term exercise at maximal intensities [21,22,27] or submaximal endurance exercise [26,29].…”
Section: Introductionmentioning
confidence: 99%
“…week standardized exercise program [22]. We hypothesized at rst that high intensity exercise could largely change AAs concentrations, since a recent reported monitored that the strongest response of serum metabolic ngerprint was seen after resistance exercise, followed by high-intensity interval exercise, while effect of continuous moderate-intensity exercise was weak in men with metabolic syndrome [28]. However, the results in our work indicated that 6 moth moderate exercise seemed more e cient on AAs metabolism improvement in a con ict with prior study, especially on BCAAs decreasing.…”
Section: Discussionmentioning
confidence: 99%